2009
DOI: 10.1163/156853909x447775
|View full text |Cite
|
Sign up to set email alerts
|

Using a behaviour discovery curve to predict optimal observation time

Abstract: Behavioural observations are vital to furthering our knowledge of species' ecology. Determining a method for formalising the length of behavioural observation time (coined Behaviour Discovery Curve) is practical for both reducing disturbance to the animals observed and limiting costs to the researcher. This paper suggests a method of calculating behaviour discovery curves, which allows researchers to estimate the optimal amount of data to collect when establishing an ethogram. The curve is fitted to a logarith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Indeed, a previous study aiming to establish the ethogram of red pandas (Ailurus fulgens fulgens) and using a similar model showed that, if the total number of observation hours exceeds the number of animals observed, and if the degree of behavioral idiosyncrasy in the population is relatively low, the number of behaviors observed per hour increases at a more rapid rate when observing several animals within an observation time than when observing one single animal for the same length of time. In other words, it is better to observe more individuals in any given observation period than one individual for a long period of time (Jule, Lea, & Leaver, 2009). Our study met these two requirements.…”
Section: Discussionmentioning
confidence: 74%
“…Indeed, a previous study aiming to establish the ethogram of red pandas (Ailurus fulgens fulgens) and using a similar model showed that, if the total number of observation hours exceeds the number of animals observed, and if the degree of behavioral idiosyncrasy in the population is relatively low, the number of behaviors observed per hour increases at a more rapid rate when observing several animals within an observation time than when observing one single animal for the same length of time. In other words, it is better to observe more individuals in any given observation period than one individual for a long period of time (Jule, Lea, & Leaver, 2009). Our study met these two requirements.…”
Section: Discussionmentioning
confidence: 74%
“…Even when animals are being observed directly, it is hard to be certain that all possible relevant behaviors have been witnessed [169], especially when extrapolating behavior in captivity to behavior in the wild. As accelerometry has matured, researchers have developed special software tools to address this obstacle and reduce the time and labor necessary for direct observation [164,170].…”
Section: Data Filters For Separating Gravitational Acceleration From mentioning
confidence: 99%